2006
DOI: 10.1016/j.jmb.2006.08.060
|View full text |Cite
|
Sign up to set email alerts
|

One Protein, Two Enzymes Revisited: A Structural Entropy Switch Interconverts the Two Isoforms of Acireductone Dioxygenase

Abstract: SummaryAcireductone dioxygenase (ARD) catalyzes different reactions between O 2 and 1,2-dihydroxy-3-oxo-5-(methylthio)pent-1-ene (acireductone) depending upon the metal bound in the active site. Ni +2 -ARD cleaves acireductone to formate, CO and methylthiopropionate. If Fe +2 is bound (ARD ′), the same substrates yield methylthioketobutyrate and formate. The two forms differ in structure, and are chromatographically separable. Paramagnetism of Fe +2 renders the active site of ARD′ inaccessible to standard NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(140 citation statements)
references
References 32 publications
9
130
0
Order By: Relevance
“…They found that substitution of the Fe(II) by Ni(II) or Co(II) significantly increased the reaction energy barrier and thus deterred the oxidization reaction (50). In the only known nickel-containing dioxygenase, Ni-ARD, the nickel is not redox-active and serves only to coordinate the substrate and facilitate ligand oxidation by O 2 (51).…”
Section: Discussionmentioning
confidence: 99%
“…They found that substitution of the Fe(II) by Ni(II) or Co(II) significantly increased the reaction energy barrier and thus deterred the oxidization reaction (50). In the only known nickel-containing dioxygenase, Ni-ARD, the nickel is not redox-active and serves only to coordinate the substrate and facilitate ligand oxidation by O 2 (51).…”
Section: Discussionmentioning
confidence: 99%
“…X-ray absorption spectroscopy (XAS) studies of the structure of the catalytic Ni center in resting NiARD enzyme and the enzyme-substrate (ES) complex have been reported (14). We have also described a structural model for FeARD' and identified a structural entropy switch that interconverts the two isoforms (15) (Figure 1). …”
mentioning
confidence: 95%
“…In both cases, the results of XAS studies of NiARD were used to determine Ni-ligand bond lengths and coordination geometry (14). The recently published FeARD' structural model is based on the structure of a stable soluble metal-free mutant of Klebsiella ARD, H98S ARD, after the serendipitous discovery that this mutant is isostructural with FeARD' as determined by multidimensional NMR experiments (15). As with NiARD, Fe-ligand bond lengths and ligation geometry was established using the results of XAS experiments that are detailed here.…”
mentioning
confidence: 99%
“…The only gene displaying an elevated mRNA transcript was At4g14716 (Arabidopsis Genome Initiative accession). To show that increased expression of At4g14716 was responsible (28,41). AdoMet is recycled into methionine via the intermediates MTA, 5-methylthioribose (MTR), and acireductone.…”
Section: Overexpression Of the Coding Region Of At4g14716 (Formally Smentioning
confidence: 99%
“…This pathway is important in that it provides the organism with a source of methionine under limiting conditions, regulates the production of polyamines, and in plants allows for the production of ethylene (26). KoARD proteins catalyze two distinct reactions dependent upon which divalent metal ion is bound in the active site (27,28). Fe-bound ARD catalyzes the on-pathway reaction that converts acireductone to the keto acid ␣-keto-␥-methylthiobutyrate (the methionine precursor).…”
Section: ϫ65mentioning
confidence: 99%